2019
DOI: 10.1007/s00125-018-4776-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of X-box binding protein 1 in Müller cells augments retinal inflammation in a mouse model of diabetes

Abstract: Aims/hypothesis Müller glia (MG) are major sources of retinal cytokines, and their activation is closely linked to retinal inflammation and vascular leakage in diabetic retinopathy. Previously, we demonstrated that X-box binding protein 1 (XBP1), a transcription factor activated by endoplasmic reticulum (ER) stress in diabetic retinopathy, is involved in regulation of inflammation in retinal endothelial cells. Now, we have explored the role of XBP1 and ER stress in the regulation of MGderived proinflammatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…In the PCV group, the one-year change in CRT indicated significant improvement in non-diabetic as compared to diabetic patients. Another study demonstrated an increase in VEGF production in murine models of retinal inflammation with diabetes as compared to those without diabetes [13].…”
Section: Discussionmentioning
confidence: 96%
“…In the PCV group, the one-year change in CRT indicated significant improvement in non-diabetic as compared to diabetic patients. Another study demonstrated an increase in VEGF production in murine models of retinal inflammation with diabetes as compared to those without diabetes [13].…”
Section: Discussionmentioning
confidence: 96%
“…17 In healthy cells, the UPR reduces ER stress levels via upregulation of ER chaperones, promotion of ERassociated degradation of misfolded proteins, and increased regulation of protein translation. 17 However, under conditions of prolonged and irremediable ER stress, the apoptotic branch of the UPR is activated, causing death of affected cells. 17,20,21 Although factors such as abnormal glucose and lipid metabolism, oxidative stress, excess cytokine release, and autophagy are likely implicated, [22][23][24] the pathophysiologic mechanism involved in the progression of DR has yet to be fully elucidated.…”
mentioning
confidence: 99%
“…17 However, under conditions of prolonged and irremediable ER stress, the apoptotic branch of the UPR is activated, causing death of affected cells. 17,20,21 Although factors such as abnormal glucose and lipid metabolism, oxidative stress, excess cytokine release, and autophagy are likely implicated, [22][23][24] the pathophysiologic mechanism involved in the progression of DR has yet to be fully elucidated. 25 Interestingly, many of these factors are regulated by pathways involved in the UPR.…”
mentioning
confidence: 99%
See 2 more Smart Citations